An Analysis of Students’ Difficulties in Writing Narrative Text at SMA WR Supratman 2 Medan - Wilianty Wilianty (ELT (English Language Teaching Prima Journal), 2024)
Abstract The objective of this research is to search and analyse the difficulties faced by the students in writing narrative text which was done by the 11th grade students at SMA WR Supratman 2 in the academic year of 2023/2024. This research used descriptive qualitative method. This research involved 23 students and 2 teachers as the research samples. The data were collected from written test and interview as the instruments. Both written test and interview were analysed to gain the result. The written exam results revealed that the majority of students faced challenges in grammar, particularly with tenses. Following grammar, students struggled with sentence structure, vocabulary, spelling, and punctuation. The data also showed that students were not accustomed to do writing that those habits shaped students’ opinion that writing is a difficult task. Consequently, students’ lack motivation in writing. Therefore, researcher suggest teachers to firstly ensure students mastery in the usage of language features before moving on to writing. Researcher also suggest students to practice writing short paragraphs, then gradually progress to longer texts.